Exploring the Root Cause of Quiet Quitting Phenomena Among Gen-Z: A Systematic Literature Review of Contributing Factors - Dika Lesmana, Anak Agung Bagus; Yunita, Putu Irma (Syntax Literate, 2025)
The phenomenon of quiet quitting has become a global concern, representing a decline in work engagement, particularly among Generation Z. This literature review aims to analyze the factors influencing the emergence of quiet quitting and to explore strategies for addressing it, drawing on findings from various international studies. This study employs a narrative review method, utilizing PubMed, Elsevier, and Google Scholar as databases to identify relevant articles. The keywords used are "quiet quitting," "Gen-Z Worker," and "Gen-Z in Workplace." The literature used is limited to the years 2015-2025. The results of the review indicate that quiet quitting is influenced by a combination of psychological factors (such as burnout and emotional well-being), organizational factors (low organizational support, unclear career paths, and lack of empathetic leadership), technological factors (digital fatigue due to excessive online workload), and generational values that emphasize work-life balance and the search for meaning. To address this phenomenon, the literature recommends multidimensional policies that include burnout prevention, increasing perceived organizational support, implementing healthy, flexible work systems, managing digital workload, and strengthening leadership capacity based on human-centric management.